Exploring the anti-acne potential of Muntingia calabura L leaves against Staphylococcus epidermidis: In vitro and in silico perspective - Aloysius Imanadi Sambi; Bakti Wahyu Saputra; Agustina Setiawati (Journal of HerbMed Pharmacology)
Introduction: Muntingia calabura is a medicinal plant possessing antimicrobial properties against various bacteria. The purpose of this study was to examine in vitro and in silico activity of the ethyl acetate fraction of M. calabura leaves against the acne-causing commensal bacterium, Staphylococcus epidermidis. Methods: In this study, M. calabura leaves were extracted using ethanol and then further fractionated with ethyl acetate. The phytochemicals in the fraction were identified with thin layer chromatography (TLC). The activity of the fraction was then tested in S. epidermidis culture using the agar diffusion method. Additionally, the molecular docking of M. calabura phytochemicals constituents was simulated to teicoplanin-associated locus regulator (TcaR) of S. epidermidis. Results: The ethyl acetate fraction of M. calabura exhibited robust antibacterial activity against S. epidermidis culture, resulting in inhibition zones ranging from 5 to 10 mm. The fraction was found to contain flavonoids, saponins, and tannins as identified constituents. Further, during the molecular docking analysis, stigmasterol and 7-methoxyflavone demonstrated binding to TcaR with a lower and comparable binding energy of -7.40 and -6.19 kcal/mol, respectively, compared to the control drug, Penicillin-G (-6.40 kcal/mol). Conclusion: M. calabura has the potential to serve as a valuable source of active phytochemical compounds for addressing acne. Further studies are needed to isolate and evaluate each compound found in M. calabura individually against S. epidermidis.